AGE SEX AND GRADE ACROSS LEVEL OF EDUCATION EFFECT ON FOREIGN LANGUAGE ANXIETY - Muhammad Yassin (UIBU, 2018)
Being designed in expost facto, this research intends to seek the answer of the following research quetions 1) is there a statistically significant effect of age, sex and grade difference on FL anxiety? 2) do females, older and lower grader participants score higher in foreign language anxiety? A research instrument, foreign language classroom anxiety scale, from Horwitz, Horwitz, Cope (1986) was distributed to collect the data about the level of FL anxiety which the participants have, the data then was analysed using independent t-test and Anova in SPSS 24. Performing independent t-test it was found that the t-value from age and sex group was 1,356 and 1,123 respectively, while sig. (two tailed) of the two group was .178 and . 264 which was more than 0.05. this mean that there was no siginificant defference of age and sex group in term of foreign language anxiety. In other word, females and older participants are no more anxious than males and younger participants, and vice versa. Different pattern appeared in the result of data analysis of the effect of grade on foreign language anxiety using Anova. The mean difference of grade group was found to be statistically significant with F-value 3.847 and sig. 0.025 where .025 was less than 0.05. This computation implied that grade is a significant predictor for foreign language anxiety. In broader explanation, it was proved that lower grade students in junior high school tend to be more anxious than the upper ones in senior high school and university.